P219 Gender Differences in GP Suggested Diagnosis For COPD in Primary Care. (19th November 2012) - Roberts, NJ; Patel, IS; Partridge, MR
Abstract : Background: Mosca et al has shown that clinicians fail to recognise cardiovascular risk in women (1). We have explored whether the same applies to COPD. Methods: Gender, demographics and symptoms were examined for patients referred by a GP to a community spirometry service with "suspected COPD or "definite COPD" over a 4 year period. These were compared with the final diagnosis after spirometry and specialist review. Results: 445 GP referrals for "suspected" or "definite COPD" (221 Males, 224 females) were reviewed. When the GP suggested a diagnosis of "definite COPD" (n=180), this was confirmed in 87.5% of men (77/88) and 73.9% (68/92) of women (p=0.022). There was a trend for women to present more frequently with allergies (p=0.055) and men with progressive breathlessness as their main symptom (p=0.051). Similarly for those with suspected COPD (n=265) 60.9% (81/133) of men and 43.2% (57/132) of women had this diagnosis confirmed (p=0.004). Women were more likely to report allergies (p=0.002), although a large percentage (81%) reported symptoms starting in later decades. Females who did not receive a diagnosis of COPD (n=75) had a lower prevalence of smoking (ex/current smokers (79%, 59/75, p=0.042) compared to women who received a diagnosis of COPD (91%, 52/57). Women who did not have COPD confirmed were likely to have a non-respiratory cause for their symptoms (45%, 34/75), normal spirometry (33%, 25/75), restrictive spirometry (13%, 10/75) and asthma (8%, 6/75). Men who did not have COPD (52/133) were likely to have normal spirometry (69%, 36/52), restrictive spirometry (15%, 8/52), a non-respiratory cause (8%, 4/52) or asthma (6%, 3/52). In this group 86% of men smoked (45/52) compared to 95% (77/81) of those with confirmed COPD. Conclusions: In GP referrals with "suspected" and "definite" COPD, there were significant differences in final diagnosis between men and women after spirometry. Women were more likely to have a GP diagnosis of COPD which was amended after spirometry. High levels of smoking were evident in both groups perhaps influencing GPs towards this, as opposed to other possible diagnoses, particularly in women. Mosca L et al. Circulation 2005; 111:499–510.